THE IMPLEMENTATION OF CASCADING IN THE REGIONAL GOVERNMENTS - Idel Eprianto; Kamaludin Kamaludin; Saiful Saiful; Fachruzzaman Fachruzzaman (LPPM STIE PERTIBA Pangkalpinang, 2021)
Cascading carried out in local governments greatly affects the performance of local governments in the Performance Accountability System for Government Agencies (SAKIP). This study aims to determine the implementation of cascading in the local government of Kerinci Regency, Jambi Province and Rejang Lebong Regency, Bengkulu Province in realizing a clean, accountable, and high-performing government. Researchers used a qualitative approach with descriptive analysis method. The results showed that in general cascading has been carried out to improve the quality of governance in Kerinci Regency, Jambi Province and Rejang Lebong Regency, Bengkulu Province. However, the application of cascading in achieving the Key Performance Indicators (KPI) of Regional Heads still needs to be revised or improved so that all Regional Apparatus Organizations (OPD) can align the KPIs of Regional Heads with KPIs of Regional Apparatus Organizations to achieve the vision and mission of the regional government. Furthermore, the linkage of the Regional Medium-Term Development Plan (RPJMD) and Local Government Work Plan (RKPD) with the Strategic Plan and Work Plan that has been running according to the rules and cascading carried out in the regional government affects the results of the regional government performance assessment in the Performance Accountability System of Government Agencies.